OUT COMES AFTER CAR T CELL THERAPY IN THE LONG RUN - Faez, Samaa (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: During the past several years, there has been a lot of discussion regarding the utilization of chimeric antigen receptor T-cells as an immunotherapy treatment for malignancies. Method: The scope of this study encompasses not only the negative consequences that CAR-T cells have, but also the mechanisms that are responsible for those effects, as well as potential treatments. Results: Through the utilization of this therapy strategy, both hematological malignancies and solid tumors have been successfully treated. However, it has been associated with a number of adverse reactions, such as cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), off-target effects, anaphylaxis, infections associated with CAR-T cell infusion (CTI), tumor lysis syndrome (TLS), B-cell dysplasia, hemophagocytic lympho histiocytosis (HLH)/macrophage activation syndrome (MAS), and coagulation disorders. Novelty: The therapeutic application of CAR-T cell therapy can be informed by this evaluation, which will furnish critical reference data.